PERENCANAAN TEBAL PERKERASAN RUAS JALAN A DI KABUPATEN LEBAK - An An Anisarida; Edward Hafudiansyah; Edi Kurniawan (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2020)
Urban and rural roads in Indonesia have increased the movement of current and volume of traffic every year. The increase in traffic should be offset by improved road infrastructure, both from quality and quantity. Jalan A is a street located in Kabupaten Lebak. Jalan A is one of the roads that is used as an alternative to infrastructure improvement in case of vehicle congestion on the main road. The existing condition of road A that occurs when experiencing severe levels of damage along the road. Based on this, it needs to be done planning improvement of road section A to fulfill the quality and performed road widening to meet the quantity. The road planning uses the method from Pt-T-01-2002-B Manual Desain Perkerasan (MDP) 2017 and AASTHO-1993 method. The resulting planning is used to provide an alternative in design calculations. The calculations obtained become a reference decision making by the stake holder in determining the design of the planning used.